2021
DOI: 10.1111/cdev.13585
|View full text |Cite
|
Sign up to set email alerts
|

Preschool‐Aged Children Jointly Consider Others’ Emotional Expressions and Prior Knowledge to Decide When to Explore

Abstract: Preschool-aged children jointly consider others' emotional expressions and prior knowledge to decide when to explore. Child Development. Online first publication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Similarly, another study involving mothers and infants interacting together with a surprise-inducing toy found that the mothers’ exclamations of surprise became more high-pitched when they noticed that their children did not react with surprise to the toy (Reissland et al, 2002). Along similar lines, Wu and Gweon (2021) introduced 3- to 4-year-old children to a novel toy with one salient casual function that the children first learned about. The children then saw an adult play with the toy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study involving mothers and infants interacting together with a surprise-inducing toy found that the mothers’ exclamations of surprise became more high-pitched when they noticed that their children did not react with surprise to the toy (Reissland et al, 2002). Along similar lines, Wu and Gweon (2021) introduced 3- to 4-year-old children to a novel toy with one salient casual function that the children first learned about. The children then saw an adult play with the toy.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the adult is already familiar with the object, even infants interpret the expression as directed toward something else (e.g., another toy or a specific part of the toy; Moll et al, 2006). By preschool years, children jointly consider another person's emotional expression (e.g., surprise vs. happiness) and prior knowledge to infer the presence of a hidden causal function of a toy and modulate their own exploration accordingly (Wu & Gweon, 2021). Other work suggests that children even use others' emotional reactions to different states of a toy (e.g., getting broken or fixed) to infer who owns the toy (Pesowski & Friedman, 2016).…”
Section: Emotion As Information About External Eventsmentioning
confidence: 99%
“…Similar inferences are seen in young children. For example, preschoolers use statistical information to infer preferences (Heck et al, 2021; Kushnir et al, 2010; see also Diesendruck et al, 2015; Ma & Xu, 2011; Vélez & Gweon, 2020) and emotions (Asaba et al, 2019; Doan et al, 2020; see also Doan et al, 2018; Wu & Gweon, 2021 for inferences about surprise). Together this growing body of findings suggests that unexpected outcomes gives rise to myriad social inferences across the life span.…”
Section: Discussionmentioning
confidence: 99%
“…We did not test children younger than age 5 because we thought they would struggle to understand the diagrams used to convey social relations. However, younger children might infer relations from mutual connections if these were presented in a different way, since infants and toddlers make statistical social inferences(Diesendruck et al, 2015;Kushnir et al, 2010;Ma & Xu, 2011;Vélez & Gweon, 2020;Wu & Gweon, 2021).2 We accidentally overlooked this exclusion criterion when preregistering this experiment. The pattern of results does not change if these seven participants are included.INFERRING RELATIONSHIPS…”
mentioning
confidence: 99%